Lensless Scheme for Measuring Laser Aberrations Based on Computer-Generated Holograms - George Krasin; Michael Kovalev; Nikita Stsepuro; Pavel Ruchka; Sergey Odinokov (Sensors, 2020)
All of the existing holographic wavefront sensors are either bulky or have low accuracy of measuring wavefront aberrations. In this paper, we present an improvement of the holographic method of measuring wavefront aberrations using computer-generated Fourier holograms. The novelty of this work lies in the proposed approach to the synthesis of Fourier holograms, which are implemented using phase-only SLM. The main advantages of this method are the increased diffraction efficiency compared to the previously known methods, and the more compact implementation scheme due to the elimination of the conventional Fourier-lens. The efficiency of the proposed method was confirmed by numerical simulation and optical experiments.